CO2 fixation and production of biodiesel by Chlorella vulgaris NIOCCV under mixotrophic cultivation. (February 2019) - Jain, Deepti; Ghonse, Supriya S.; Trivedi, Tanmay; Fernandes, Genevieve L.; Menezes, Larissa D.; Damare, Samir R.; Mamatha, S.S.; Kumar, Sanjay; Gupta, Vishal
Graphical abstract: Highlights: Synergy of CO2 sequestration, wastewater utilization, and biofuel production. Higher CO2 tolerant strain Chlorella vulgaris NIOCCV. CO2 tolerance up to 20% at continuous flow rate of 0.5 vvm. Lipid accumulation up to 38% on dry biomass weight basis. Promising feedstock for saline effluent treatment and utilization for biodiesel production. Abstract: In this study, Chlorella vulgaris NIOCCV was cultivated in seafood processing industry wastewater with continuous supply of 5%, 10%, and 20% CO2 . The optimum CO2 fixation efficiency ( R CO 2 ), biomass productivity, specific growth rate (SGR), and lipid content recorded were 0.43 mg L −1 d −1, 264.58 ± 8.8 mg L −1 d −1, 0.46 d −1, and 38 ± 2.6% on dry weight basis, respectively at CO2 supply of 10%. The fatty acid methyl ester-derived biodiesel properties determined at same condition were in compliance with national and international fuel standards. The higher calorific value (HHV) of the resultant biomass was 11.14, 16.41 and 12.83 MJ Kg −1 for CO2 enrichment of 5%, 10%, and 20%, respectively. The synergistic environmental benefit of nutrients removal from wastewater is shown as an additional advantage of microalgal cultivation. Thus, integration of algae-based CO2 fixation with wastewater treatment and biodiesel production may realize microalgal CO2 capture technology as environmentally sustainable and economically more attractive.